Words into action: bridging the gap between theory and practice when supporting young people in care - Olivia Roles; Lorraine Johnstone (Scottish Journal of Residential Child Care)
The authors elucidate Johnstone's ABC Formulation Framework and 6D model for understanding and intervening with young people who display distressed behaviour. This approach equips care professionals with a theoretically informed method of identifying unmet needs that drive harmful behaviours. By simplifying complex psychological theories, the approach empowers practitioners to apply best practices effectively. The authors describe the implementation of this framework in the secure care context at Rossie Young People’s Trust, providing a clear account of its transformative impact on both staff and young people.